Childhood necrotising pneumonia, empyema and complicated parapneumonic effusion secondary to community acquired pneumonia: report of 158 cases from a tertiary hospital in Egypt - Salma Abdelhady; Amira A. Moharram; Zainab Fawzy; Eman Fouda (Respiratory Research)
Abstract Background Incidence of childhood complicated community acquired pneumonia (cCAP) is increasing worldwide. Necrotising pneumonia (NP), empyema and complicated parapneumonic effusion (CPPE) are the most common local complications. Methods This retrospective observational study describes clinical characteristics, aetiology and management of children hospitalized with cCAP in one of the largest tertiary centers in Egypt, over 5 years (December 2017 till September 2022). Results A total of 158 cases were identified. Seasonal variation was observed, as more cases were hospitalized during Winter and Spring. NP, empyema and CPPE, were diagnosed in 85 (54%), 52 (33%) and 21 (13%) children, respectively. 54 (64%) of children presented with NP had associated empyema or CPPE. The yield of pleural fluid, sputum and blood cultures were 23%, 18% and 17%, respectively. Community acquired MRSA was the predominant causative organism, followed by S pneumoniae. 87% of the patients had pleural interventions. 29 (18%) children received fibrinolytics. Three children presented with CAP and highly septated effusion, developed NP and persistent air leaks following fibrinolytic administration. Patients had prolonged hospitalization (median 17 days). 15 (10%) children had surgery. Children presented with NP had more morbidities and longer length of hospital stay, compared to children presented with CPPE and empyema. ICU admission, mechanical ventilation, severe anemia requiring blood transfusion, broncho-pleural fistula and surgical interventions were significantly higher in NP cohort. We report 5 mortalities, 4 of them below 1 year of age. Conclusions This study describes the largest cohort of children hospitalized with cCAP from Egypt till this date. Management of cCAP remains challenging worldwide and the current guidelines requires updating. Improvement of microbial detection and reporting is needed to promote antimicrobial stewardship.